Problems of the establishment of worship houses in Pati, Central Java - Sulaiman Sulaiman (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
This research aimed to know the problems of establishment of worship houses in Pati Central Java. This research used a qualitative approach with the collecting data interview, observation, and documen review. This research was expected to give information and theoritical study materials for the general public, especially those related to policy on the establishment of worship houses. The results showed that establishment of worship houses is often a clash beetween the formal regulation and social regulation, because of differences in interpretation of legislation. The establishment of worship houses take place smoothly and individual appproach with good. In contrast, the establishment of worship houses are often hampered by resistance citizens of community, but goverment does not give a definite decision “accepted” or “rejected”. This resulted in the establisment of worship houses stagnant and impressed omission.Keywords : Houses of worship - formal regulation - social conflict